Composite resin color stability: influence of light sources and immersion media (Journal of Applied Oral Science, 2011)
OBJECTIVE: This study evaluated the influence of light sources and immersion media on the color stability of a nanofilled composite resin. MATERIAL AND METHODS: Conventional halogen, high-power-density halogen and high-power-density light-emitting diode (LED) units were used. There were 4 immersion media: coffee, tea, Coke® and artificial saliva. A total of 180 specimens (10 mm x 2 mm) were prepared, immersed in artificial saliva for 24 h at 37±1ºC, and had their initial color measured with a spectrophotometer according to the CIELab system. Then, the specimens were immersed in the 4 media during 60 days. Data from the color change and luminosity were collected and subjected to statistical analysis by the Kruskall-Wallis test (p